Specific cannabinoids revive adaptive immunity by reversing immune evasion mechanisms in metastatic tumours - Dada, Sarah; Ellis, Samantha L. S.; Wood, Christi; Nohara, Lilian L.; Dreier, Carola; Garcia, Nicolas H.; Saranchova, Iryna; Munro, Lonna; Pfeifer, Cheryl G.; Eyford, Brett A.; Kari, Suresh; Garrovillas, Emmanuel; et al. (Frontiers in Immunology, 2023)
Emerging cancers are sculpted by neo-Darwinian selection for superior growth and survival but minimal immunogenicity and a common signature across metastatic cancers is evasion of immune surveillance. Immune subversion in metastatic tumours can be achieved through several mechanisms, one of which involves loss of expression or mutation of genes composing the MHC-I antigen presentation machinery (APM) that render tumours invisible to the adaptive immune response. Fascinating ethnographic and experimental findings indicate that cannabinoids inhibit the growth and progression of several categories of cancers however, the mechanisms underlying these observations remain clouded in uncertainty. Here, we screened a library of cannabinoid compounds and found molecular selectivity amongst specific cannabinoids, where related molecules such as Δ9-tetrahydrocannabinol, cannabidiol, and cannabigerol can reverse the metastatic immune escape phenotype in vitro by inducing MHC-I cell surface expression in a wide variety of metastatic tumours that subsequently sensitizing tumours to T lymphocyte recognition. Remarkably, H3K27Ac ChIPseq analysis established that cannabigerol and gamma interferon induce overlapping gene signatures and key gene pathways that are activated in cannabigerol-treated metastatic tumours related to cellular senescence and APM genes involved in revealing metastatic tumours to the adaptive immune response. Overall, the data suggest that specific cannabinoids may have utility in cancer immunotherapy regimens by overcoming immune escape and augmenting cancer immune surveillance in metastatic disease. Finally, the discovery of ability of cannabinoids to alter epigenetics programs, may elucidate many of the pleiotropic medicinal effects of cannabinoids on human physiology.